Evolution of A(H1N1) pdm09 influenza virus masking by glycosylation. (4th May 2021) - Ge, Pan; Ross, Ted M.
ABSTRACT: Introduction : As the pathogen that caused the first influenza virus pandemic in this century, the swine-origin A(H1N1) pdm09 influenza virus has caused continuous harm to human public health. The evolution of hemagglutinin protein glycosylation sites, including the increase in number and positional changes, is an important way for influenza viruses to escape host immune pressure. Based on the traditional influenza virus molecular monitoring, special attention should be paid to the influence of glycosylation evolution on the biological characteristics of virus antigenicity, transmission and pathogenicity. The epidemiological significance of glycosylation mutants should be analyzed as a predictive tool for early warning of new outbreaks and pandemics, as well as the design of vaccines and drug targets. Areas covered : We review on the evolutionary characteristics of glycosylation on the HA protein of the A(H1N1)pdm09 influenza virus in the last ten years. Expert opinion : We discuss the crucial impact of evolutionary glycosylation on the biological characteristics of the virus and the host immune responses, summarize studies revealing different roles of glycosylation play during host adaptation. Although these studies show the significance of glycosylation evolution in host-virus interaction, much remains to be discovered about the mechanism.